The message of James the tests of faith - Motyer, J. Alec (Leicester, UK IVP, 1985)
Includes bibliographical references.
Copy 2 : "The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990".
Keywords: Bible. N.T. James -- commentaries